2008
DOI: 10.1177/0032885507310999
|View full text |Cite
|
Sign up to set email alerts
|

Administrative Segregation From Within

Abstract: The growth of the inmate population nationwide has given rise to supermax prisons over the past two decades. Among the controversial issues that supermax prisons face are concerns about the types of individuals placed in solitary confinement and the arbitrary nature of those placements. This study profiled inmates in administrative segregation, as supermax confinement is called in Colorado, and the process and reasons for their placement. Evidence of institutional misbehavior, more serious criminal histories, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 20 publications
0
58
0
Order By: Relevance
“…In correctional terminology, ADSEG is often referred to as ''security housing unit,'' ''control unit,'' or ''intensive management unit;'' terms which typify the most restrictive housing setting a prisoner can be placed in. Such settings may either be entire facilities or units (or blocks) at variously defined maximum security or supermax facilities (Arrigo & Bullock, 2008;Boin, 2001;Cloyes, 2007;Naday, Freilich, & Mellow, 2008;O'Keefe, 2008;Pizarro & Narag, 2008). That is, certain prisons or units referred to as maximum security may in actual practice be conducted as supermax facilities.…”
Section: Administrative Segregation and Who Gets Placed Therementioning
confidence: 99%
See 2 more Smart Citations
“…In correctional terminology, ADSEG is often referred to as ''security housing unit,'' ''control unit,'' or ''intensive management unit;'' terms which typify the most restrictive housing setting a prisoner can be placed in. Such settings may either be entire facilities or units (or blocks) at variously defined maximum security or supermax facilities (Arrigo & Bullock, 2008;Boin, 2001;Cloyes, 2007;Naday, Freilich, & Mellow, 2008;O'Keefe, 2008;Pizarro & Narag, 2008). That is, certain prisons or units referred to as maximum security may in actual practice be conducted as supermax facilities.…”
Section: Administrative Segregation and Who Gets Placed Therementioning
confidence: 99%
“…Greater risk of prisoner maladjustment and SIB in ADSEG is generally assumed (Bonta & Gendreau, 1990;Correctional Association of New York, 2004;Craig, 2003;Haney, 1993;Haney & Lynch, 1997;Johnson, 1976;532 E. Lanes O'Keefe, 2008;Rhodes, 2005;Salive, Smith, & Brewer, 1989;Sykes, 1958). Consider, however, the findings that (a) a majority of all successful prisoner suicides occur in segregation housing (Mumola, 2005;White, Schimmel, & Frickey, 2002), (b) mentally ill prisoners find themselves housed for longer periods of time in ADSEG than nonmentally ill prisoners (Correctional Association of New York, 2004;Stone, 2003), and (c) many prisoners in ADSEG are relatively younger, less educated, more prone to substance abuse, have more extensive offense histories, and are more impulsive and hostile, easily frustrated, and experience higher rates of housing problems within prison than nonsegregated prisoners (Haney, 1993;Lovell, Cloyes, Allen, & Rhodes, 2000;Motiuk & Blanchette, 1997;O'Keefe, 2008;Sykes, 1958;Toch & Kupers, 2007;Zinger & Wichmann, 1999).…”
Section: Administrative Segregation and Who Gets Placed Therementioning
confidence: 99%
See 1 more Smart Citation
“…With these observations in mind, and heeding the calls of recent supermax research and reviews (e.g., Cloyes et al, 2006;Kurki & Morris, 2001;Mears, 2008;O'Keefe, 2008;Pizarro & Narag, 2008;Ward & Werlich, 2003), the goal of this exploratory study was to contribute to scholarship on how supermax housing is used. To this end, it provides what the authors believed to be the first study both to quantify several critical dimensions of the supermax experience, including the frequency of placement into supermax confinement, the duration of such confinement, and the timing of supermax incarceration prior to reentry, and to examine factors, including demographic characteristics, prior record, and measures of in-prison behavior, that may contribute to placement in supermax housing.…”
Section: Concerns About Supermax Incarcerationmentioning
confidence: 99%
“…A prominent criticism of supermax incarceration is that placement decisions are arbitrary (Mears & Watson, 2006;Riveland, 1999). Several studies described some inmates already in supermax housing (e.g., Cloyes et al, 2006;Lovell, Cloyes, Allen, & Rhodes, 2000;Lovell et al, 2007;O'Keefe, 2008) and found that they appeared to have histories of infractions and violent behavior that are greater than those of general population inmates. They left open, however, the question of whether the characteristics of the inmates, different types of infractions, as well as behavioral histories, are linked to administrator's decisions to place inmates in such housing, and they did not adjust for differences in the lengths of supermax inmates' and general populations inmates' prison terms, respectively.…”
Section: Research Gaps On Supermax Incarcerationmentioning
confidence: 99%